Analisis Implementasi Model PACE pada Mata Kuliah Statistika Matematika - Andri Suryana (Universitas Indraprasta PGRI, 2015)
Mathematical Statistics is one of course that are considered difficult by students so lecturer need implement an appropriate learning model. One of the learning model that can be implemented in this course is PACE model. PACE Model is one of the learning model based on constructivism which has phases: project, activity, cooperative learning, and exercise. The aim of this research is analyzing the implementation of the PACE model in mathematical statistics courses. The subject of this research is students of Mathematics Education at one of the private universities in East Jakarta who contracted mathematical statistics 2 courses. The method used is qualitative. The results of this research is generally seen that implementation of PACE model in this course is good.